2020
DOI: 10.1001/jamapsychiatry.2019.2914
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bulimia Nervosa With Long-term Risk of Cardiovascular Disease and Mortality Among Women

Abstract: IMPORTANCE Bulimia nervosa is associated with short-term cardiovascular complications in women, but its long-term consequences on cardiovascular health are unknown.OBJECTIVE To study the association of bulimia nervosa with the long-term risk of cardiovascular disease and mortality in women. DESIGN, SETTING, AND PARTICIPANTSIn this longitudinal cohort study, 416 709 women hospitalized in Quebec, Canada, including women hospitalized for bulimia nervosa and those for pregnancy-related events as a comparison group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…This short period of time is not uncommon among dieters on very low caloric diets. These findings support a recent study by Tith et al (2019) that followed women with bulimia nervosa for up to 12 years and found a striking increase in the risk of cardiovascular disease, including ischaemic heart disease, atherosclerosis and cardiac conduction defects. Thus, our studies in rats warrant investigation of cardiovascular function in individuals subjected to short periods of sFR either because of crash dieting or other causes (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This short period of time is not uncommon among dieters on very low caloric diets. These findings support a recent study by Tith et al (2019) that followed women with bulimia nervosa for up to 12 years and found a striking increase in the risk of cardiovascular disease, including ischaemic heart disease, atherosclerosis and cardiac conduction defects. Thus, our studies in rats warrant investigation of cardiovascular function in individuals subjected to short periods of sFR either because of crash dieting or other causes (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Caloric intake can also be inadequate for other voluntary reasons (e.g. bulimia nervosa; Tith et al, 2019) or involuntary reasons (e.g. poverty, natural disasters, war).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with AN show severe underweight, and other psychiatric complications include depression and anxiety [7,193]. An increasing number of studies indicate that individuals with BN and binge eating disorders have higher incidence rates of obesity and related metabolic diseases, such as type 2 diabetes and cardiovascular disease compared to individuals with no history of eating disorders [194][195][196].…”
Section: Clinical Relevancementioning
confidence: 99%
“…Among a longitudinal cohort of 1,298,890 women from the Maintenance and Use of Data for the Study of Hospital Clientele registry 4 in the province of Quebec, Canada, we identified women admitted to hospital for anorexia nervosa between 1989 and 2016. A comparison group of women of similar age who presented for either delivery or pregnancy termination and were representative of the large majority of women in Quebec was also identified.…”
Section: Anorexia Nervosa and The Long-term Risk Of Mortality In Womenmentioning
confidence: 99%